Alam Semesta Dalam Pandangan Filosofi Islam Dan Ahli Tafsir - Muhammad Soleh Ritonga (Al Ashriyyah, 2018)
All of God's creation is often called the universe with creatures, creatures consisting of inanimate objects or living things. The Islamic view of the universe is very interesting, especially Islamic philosophical views and Tafsir experts. In the philosophical view of Islam, Some of them thought that they used the Greek heritage theory, but there are also those who din't use it. The interpreter's thought about the universe cannot be separated from the statements of the verse of the Qur'an related to the universe and its creation.